PENGARUH THIN CAPITALIZATION, TRANSFER PRICING, SALES GROWTH, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE : (Studi Kasus Pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Muhamad Abdul Latif; Ajimat Ajimat (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of thin capitalization, transfer pricing, sales growth and capital intensity on tax avoidance in property and real estate companies listed on the IDX in 2017-2021. This type of research is quantitative associative, which are testing the influence of two or more variables on other variables. The type of data used is secondary data, namely financial statement data obtained from the IDX. The sampling method in this study used porpusive sampling techniques with certain criteria. The amount of data obtained in this study was 45 from 9 companies for the 2017-2021 period. Testing in this study was assisted by EViews 9 software, and the model used was Fixed Effect Model (FEM) panel data regression. The results of this study show that simultaneously thin capitalization, transfer pricing, sales growth and capital intensity together affect tax avoidance. While partially thin capitalization does not affect tax avoidance, transfer pricing does not affect tax avoidance, sales growth does not affect tax avoidance and capital intensity has a positive effect on tax avoidance.